Deteksi Fraudulent Financial Statement melalui Dechow F-Score dengan Pemoderasi Firm Size - Mentari, Citra; Indriani, Eni (Owner : Riset dan Jurnal Akuntansi, 2024)
Financial statement fraud is common in Indonesia, especially in the financial sector. The focus of this research is to evaluate whether the six elements of the fraud hexagon theory affect the false financial statements of companies in the financial industry. These six elements are proxied by the variables stimulus (financial stability), opportunity (ineffective monitoring), rationalization (auditor switching), capability (change in director), ego (arrogance), and collusion. This study also statistically analyzes whether firm size can moderate the influence of these variables. The research population includes all financial companies listed on the Indonesia Stock Exchange in 2020–2022, both banking and non-banking subsectors. The purposive sampling method was used as a sample selection, and a total of 288 data points from 96 companies were collected. E-Views 12 software was used for data analysis. The coefficient of determination test, moderation test, hypothesis test (F and t), panel regression (chow and lagrange multiplier), and descriptive statistical analysis are the methods used to analyze the data. The results show that almost all independent variables in this study do not have a significant effect on fraudulent financial statements; the only variable that has a positive coefficient value is the auditor switching variable. The moderation test results show that company size as a moderating variable decreases the effect of auditor switching on unauthorized financial statements. However, firm size cannot moderate factors such as financial stability, ineffective monitoring, a change in director, arrogance, and collusion. Keywords: Financial Sector; Firm Size; Fraud Hexagon; Fraudulent Financial Statement